Titanium Dioxide Mesoporous Electrodes for Solid‐State Dye‐Sensitized Solar Cells: Cross‐Analysis of the Critical Parameters. Issue 9 (17th March 2014) - Colella, Silvia; Orgiu, Emanuele; Bruder, Ingmar; Liscio, Andrea; Palermo, Vincenzo; Bruchmann, Bernd; Samorì, Paolo; Erk, Peter
<x xml:space="preserve">Abstract</x> We report a comparative study on the use of four different mesoporous titanium dioxide (TiO2) photo‐electrodes for the fabrication of solid‐state dye‐sensitized solar cells (sDSSCs). The photovoltaic parameters of the device correlate with several intrinsic properties of the film, based not only on its morphological features, as commonly considered in standard characterizations, but also on the transport and the electronic properties of the photo‐electrode. These properties differ significantly for TiO2 electrodes processed using different colloidal pastes, and are decisive for the photovoltaic efficiency, ranging from 3.7% up to 5.1%. In particular, the dielectric permittivity of each mesoporous layer (εeff) and the number of traps (Nt) determined by the space‐charge‐limited current (SCLC) theory are found to be a bottle‐neck for the charge transport, greatly influencing the fill factor (FF) and open circuit voltage (Voc) of the cells. In addition, a direct correlation between TiO2 surface potential with the Voc was established. Cross‐analysis of key macroscopic parameters of the films prior to integration in the devices, in particular focusing on the determination of the capacitance and surface potential shift of the TiO2 mesoporous anode, represents a straightforward yet powerful method to screen and select the most suitable TiO2 for applications in sDSSCs.